Incidencia y factores asociados de Helicobacter pylori en la población infantil del departamento de Cajamarca - Perú’ - Calderón Rivera, Andrea Ximena (2016)
Background: The prevalence of H. pylori is greater than 50% in low development countries. In children, infection with H. pylori produces effects such as low height, impairment in growth especially in pubertal age. Polymerase Chain Reaction has a high sensitivity and specificity of 89.6% and 100% respectively, compared to other invasive methods. The objective of this study is to determine the frequency of patients with presence of H. pylori in asymptomatic children in a rural community in the north of Peru, using PCR technique in stool samples. Methods: A cross-sectional study with a convenience sampling was performed, resulting in 147 children aged between 6-14 years old of the district of San Pablo in Cajamarca, Peru. Using stool samples H. pylori DNA was obtained, then PCR amplification was done, and sequencing those with positive results, in an agreement with Macrogen, Seoul - Korea. Results: It was found a frequency of H. pylori positive cases of 21.1% with a CI 95% of 14.8 to 28.6. It was found a frequency (p=0.01) of positive for H. pylori among males (29% IC95: 19.1- 40.5) compared to women (12.7%; IC95: 6.0-22.7). There was no statistically significant differences between those positive and negative patients with H. pylori compared to age (p = 0.57), presence of overweight (p = 0.09), or excreta disposal (p = 0.71). It was not found significance difference among other variables. Conclusion: Our study found a high frequency of H. pylori determined by a molecular test with high sensitivity and specificity, demonstrating the feasibility of its implementation in rural communities. It can be considered as a tool for surveillance in areas of high prevalence of H. pylori infection.